노안환자에서 비구면 미세단안시 라식수술 및 단안시 굴절수술의 임상결과 비교 - 이수찬(Su chan Lee); 장철원(Cheol won Jang); 공석준(Seok Joon Kong); 김재우(Jae Woo Kim); 조영주(Young Joo Cho); 임태형(Tae Hyung Lim); 최기용(Kee Yong Choi); 조범진(Beom Jin Cho) (Daihan angwa haghoi jabji, 2016)
목적: 노안이 동반된 근시환자에서 비구면 미세단안시 라식 수술(laser blended vision, LBV) 및 고식적 단안시 레이저 굴절 수술(monovision laser refractive surgery)의 효능과 안정성을 비교 분석하고자 하였다. 대상과 방법: LBV를 시행 받은 환자 21명 42안, monovision을 시행 받은 환자 25명 50안을 대상으로 후향적으로 비교하였다. 술 전과 술 후 3개월 원거리, 중간거리, 근거리 시력과 굴절력 변화를 단안과 양안 모두에서 조사하였으며 LBV군에서는 추가로 술 후 3개월에 구면수차를, 술 후 3-6개월에 환자 만족도를 조사하였다. 결과: 평균연령은 LBV군에서 47.9세, monovision군에서 41.7세였다. 술 후 3개월에 구면 대응치는 LBV군에서 우세안 +0.11 ± 0.17D, 비우세안 -1.52 ± 0.36D인 반면, monovision군에서는 우세안 +0.23 ± 0.26D, 비우세안 -0.82 ± 0.28D였다. 술 후 양안 원거리나안시력의 경우 두 군 모두 minimal angle of resolution (logMAR) 시력으로 0.10보다 좋은 경우가 100%였으며, 중간거리 나안시력의 경우 0.10 이상은 LBV군에서 86%, monivision군에서 100%였다. 근거리 나안시력은 LBV군에서 0.18 이상이 95%, monovision군에서 100%였다. LBV군에서 수술 전보다 수술 후 평균 구면 수차는 증가하였으나 통계적으로 유의하지 않았다. 술 후 최대 교정시력저하나 각막 혼탁 등 시력저하가 발생할 수 있는 합병증은 두 군에서 모두 없었으며 전반적인 환자의 만족도는 LBV군에서 80%였다. 결론: 노안이 동반된 근시 환자에서 LBV는 상대적으로 높은 연령에도 불구하고 monovision과 비슷한 결과를 보였으며 효과적이고 안전한 수술방법으로 생각된다. Purpose: To compare the efficacy and safety of Laser Blended Vision (LBV) and monovision laser refractive surgery (monovision) for presbyopia correction in patients with myopia. Methods: This retrospective comparative study included 42 eyes of 21 patients with LBV and 50 eyes of 25 patients with monovision. Monocular and binocular distance, intermediate and near visual acuity, and refractive changes were evaluated preoperatively and 3 months after the surgery and compared. The patients in the LBV group underwent further evaluation of spherical aberration 3 months after the surgery and treatment satisfaction 3-6 months after the surgery. Results: The mean age of the patients was 47.9 years in the LBV group and 41.7 years in the monovision group. Three months after surgery, the spherical equivalents were +0.11 ± 0.17 D in the dominant eye and -1.52 ± 0.36 D in the non-dominant eye in the LBV group. In contrast, the spherical equivalents were +0.23 ± 0.26 D in the dominant eye and -0.82 ± 0.28 D in the non-dominant eye in the monovision group. All patients achieved a binocular uncorrected distance visual acuity of 0.10 (log MAR) or better, and 86% of the LBV group and 100% of the monovision group achieved a binocular uncorrected intermediate visual acuity of better than 0.10. Moreover, 95% of the LBV group and 100% of the monovision group achieved a binocular uncorrected near visual acuity of better than 0.18. In the LBV group, mean spherical aberration increased after surgery than before, but it was not statistically significant. Complications such as corneal opacity that could decrease visual acuity were absent in both groups. Overall patient satisfaction after surgery was 80% in the LBV group. Conclusions: Despite the relatively higher mean age of the LBV group, both groups showed similar results regarding presbyopia correction in patients with myopia. KCI Citation Count: 0